Relationships between percent body fat, body fat distribution and blood lipid, glucose, basaI insülin levels as well as cholinesterase activities (Annals of Medical Research, 2021)
None
Keywords: s : Percent body fat, bodv fat distribution, obesity, cardiovascular risk factors, cholinesterase